Implementasi Surat Pernyataan Kesanggupan dan Pemantauan Lingkungan Hidup (SPPL) di Kabupaten Banyumas - Dwi Istiningsih; Eddy Poerwodihardjo (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2017)
In conducting business or activity, there are legislation that must be obeyed. In the context of environmental regulations, there are several types of documents that must be made by business actors / development activities.One of these documents is SPPL or Statement of Environmental Management and Monitoring.During the construction and after the development activities are completed there will be some negative impacts on the environment, both on the biotic environment, abiotic and socio-cultural surrounding communities. Whereas there should be no adverse environmental impact, if the SPPL is really implemented properly.The environment minister has drafted a regulation on guidelines for the preparation of environmental documents containing the plan of action and activities to be undertaken by the initiator during and after the building activities. Here the author limits on the discussion of article 1, paragraph 3, which is about the Statement of Environmental Management and Monitoring Capacity.The potential environmental impacts, management and monitoring of environmental impacts shall be the responsibility of the developer but Implementation of the Statement of Environmental Management and Monitoring Statement has not been fully implemented by the initiating party.Officers have not conducted effective and continuous monitoring of SPPL implementation by the proponent. This results in the initiator often not passing on the matters contained in the SPPL, and is merely a formality only as a condition of the permit of the IMB.There is an